Novel techniques in sensory characterization and consumer profiling - Varela, Paula (Varela Tomasco); Ares, Gaston (Boca Raton : CRC Press, 2014)
'Sensory characterization is one of the most powerful, sophisticated and extensively applied tools in sensory science. This book focuses on sensory characterization of food and non-food products, providing an overview of classical and novel alternative methodologies. A complete description of the methodologies would be provided. Each description would be accompanied by detailed information for their implementation, discussion of examples of applications and case-studies. The implementation of the majority of the methodologies would be performed in the statistical free software R, which would make the book very useful for people non-familiar with complex statistical software'--
'Preface Sensory characterization is one of the most powerful, sophisticated, and extensively applied tools in sensory science, both in the academy and the industry. It aims at providing a complete description of the sensory characteristics of products. Sensory characterization is extensively applied in industry for the development and marketing of new products, the reformulation of existing products, the optimization of manufacturing processes, the monitoring of sensory characteristics of the products available in the market, the implementation of sensory quality assurance programs, the establishment of relationships between sensory and instrumental methods, and for estimating sensory shelf life. Descriptive analysis techniques, such as QDA
Includes bibliographical references and index.
Keywords: Food -- Sensory evaluation; Sensory evaluation; Marketing research; New products; TECHNOLOGY & ENGINEERING / Food Science